Determining the predictive importance of the core dimensions of nation brands - Lahrech, Abdelmounaim (2023)
Purpose– Informed by the resource-based and resource-advantage theories, this study, a comparative study, aims to examine the core dimensions of nation brands– culture, tourism, exports, foreign direct investment, migration and governance– from the company-based brand equity perspective in a sample of 48 countries clustered into three groups (strong, moderate and weak nation brands) from 2011 to 2019 to identify the most critical predictors of nation brand strength in each cluster. Design/methodology/approach– A clustering technique was applied to the modified Country Brand Index to cluster the included countries into strong, moderate and weak nation brands. The authors were then able to analyze each cluster in an effort to explore the relative importance of the predictor variables and determine if that importance varied across the clusters. Findings– This approach revealed novel findings of great importance to policymakers and academics. The results indicate the resources that contribute the most to nation brand equity in each cluster. Such information can guide policymakers in effectively leveraging these strategic resources. First, the cultural dimension was a more critical predictor concerning countries with moderate and weak nation brands than countries with strong brands. Second, tourism exhibited the highest predictive importance concerning all the clusters. For academics, these findings help foster a better understanding of the determinants of nation brand strength, as aligned with the resource-based and resource-advantage theories. Originality/value– The findings of this study contribute to the literature concerning nation brand management, particularly the stream related to nation brand equity monetization.